Three guys named Mike - Walters, Charles, 1911-1982; Sheldon, Sidney; Wyman, Jane, 1917-2007; Johnson, Van, 1916-2008; Metro-Goldwyn-Mayer.; Loew's Incorporated; Cinetel Films ([Los Angeles, CA] : Metro Goldwyn Mayer : Lowe's Incorporated, 1951)
A stewardess becomes romantically involved with an airline pilot, a college professor, and a successful businessman, all of whom are named Mike. When the three find out about each other, she has to decide which one she loves the most. --
"From suggestrions made by Ethel "Pub" Wells."
Jane Wyman, Van Johnson, Howard Keel, Barry Sullivan.
Director of photography, Paul C. Vogel; editor, Irvine Warburton; music, Bronislau Kaper.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 9, 2015)
Keywords: Flight attendants -- Drama; Roommates -- California -- Los Angeles -- Drama; Marriage proposals -- Drama; Comedy films; Feature films; Internet videos; Streaming video